Antistatic polyetheretherketone composite film and preparation method and application thereof
The nano-carbon fiber-loaded indium tin oxide composite material prepared by using coaxial spinning method and solvothermal method in polyether ether ketone materials, and the preparation of polyether ether ketone containing amino and carboxyl pendant groups through polymerization, the problem of poor dispersion of conductive fibers is solved, significantly improving the material's conductivity and interface binding ability, and meeting the high-demand anti-static properties.
Patent Information
- Application Number
- CN202411755038.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In the prior art, the single-form conductive fibers have poor dispersion in polyether ether ketone materials, resulting in limited anti-static properties of composite materials and cannot meet high application scenarios such as semiconductor manufacturing and electronic packaging.
Nanocarbon fiber indium tin oxide composite material (In2O3•SnO2@CF) was prepared by coaxial spinning method and solvothermal method, and polyether ether ketone containing amino and carboxyl group was prepared through polymerization to enhance the interfacial binding ability of the material.
It significantly improves the conductivity of the material, enhances the interface bonding ability, improves the anti-static performance and stability, and meets high-demand application scenarios.
Smart Images

Figure CN119220082B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrostatic protection materials, and in particular to an antistatic polyetheretherketone composite film and a preparation method and application thereof. Background Art
[0002] With the increasing popularity of electronic devices, damage caused by electrostatic discharge has gradually become a major hidden danger in the electronics industry. This static electricity phenomenon is particularly significant in high-tech fields, such as semiconductor manufacturing, electronic component assembly, and other environments that require precise operations. In order to effectively prevent the harm caused by static electricity to equipment and personnel, various anti-static materials have been developed one after another, covering conductive plastics, coating materials, and composite materials. Among them, polyetheretherketone is regarded as one of the preferred anti-static materials due to its high resistivity and excellent chemical stability. The resistivity of polyetheretherketone is as high as 10 14 Ω·cm, which can effectively inhibit the accumulation of static electricity and provide reliable anti-static protection. However, polyetheretherketone itself is a good insulating material, and its internal static dissipation speed is slow, which is easy to cause the risk of electrostatic discharge.
[0003] In order to solve the above problems, the method of adding conductive fibers (carbon fiber, glass fiber, carbon black, etc.) into polyetheretherketone is usually adopted, and the conductivity of the conductive fibers is used to provide a channel for the static discharge inside the material. These conductive fibers can not only improve the conductivity of the material, but also maintain its excellent chemical stability while enhancing the mechanical properties of the material. However, the traditional single-form conductive fibers have problems such as low current propagation rate and poor interface bonding ability with the polyetheretherketone matrix, which leads to a certain degree of weakening of the antistatic performance of the composite material, and cannot meet the application scenarios with very high antistatic requirements such as semiconductor manufacturing and electronic packaging. Therefore, researchers have tried to improve the interaction between the conductive filler and the polyetheretherketone matrix by optimizing the composite application of the conductive filler and performing surface modification, and enhance the dispersibility and bonding ability of the conductive filler in the polyetheretherketone matrix, but the effect is still affected by the type of filler, the modification method and the complexity of the composite processing technology, so it is necessary to further explore the synthesis strategy of antistatic polyetheretherketone composite materials. Summary of the invention
[0004] In order to solve the problem of poor dispersion of single-form conductive fibers in polyetheretherketone materials in the prior art, the present invention proposes an antistatic polyetheretherketone composite film and a preparation method and application thereof. The technical solution of the present invention is as follows:
[0005] An antistatic polyetheretherketone composite film comprises the following components in parts by weight: 10-40 parts of In2O3•SnO2@CF, 60-90 parts of polyetheretherketone containing amino and carboxyl side groups, 1-3 parts of silane coupling agent, 1-3 parts of lubricant, and 3-10 parts of film-forming agent.
[0006] The above In2O3•SnO2@CF was prepared by the following steps:
[0007] S1: Pour polyacrylonitrile evenly into N,N-dimethylformamide solution, stir thoroughly, and obtain a precursor spinning solution; then pour polyvinyl pyrrolidone evenly into N,N-dimethylformamide solution, stir thoroughly, and obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, perform coaxial electrospinning, and collect to obtain fiber filaments;
[0008] S2: The collected fiber filaments are placed in a crucible and transferred into a vacuum tube furnace. The temperature is raised to 550°C in a nitrogen atmosphere and then calcined at a constant temperature. After the calcination, the fiber filaments are naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0009] S3: The hollow carbon fiber, InCl3 and SnCl4 are uniformly added into a 50% ethanol aqueous solution and stirred. After the stirring, the mixture is transferred into a Teflon stainless steel high-pressure reactor for reaction. After the reaction, the precipitate is washed with anhydrous ethanol and deionized water and dried overnight to obtain In2O3•SnO2@CF;
[0010] Furthermore, the stirring time in S1 is 2 to 8 h;
[0011] Further, the flow rates of the structure carrier emulsion and the precursor spinning solution in S1 are 0.1 mL / min and 0.2 mL / min, respectively;
[0012] Further, the spinning voltage of the coaxial electrospinning in S1 is 15-25 kV;
[0013] Furthermore, the distance between the double nozzle needle of the coaxial spinning machine in S1 and the drum collector is 10-25 cm;
[0014] Further, the heating rate in S2 is 5°C / min;
[0015] Furthermore, the constant temperature calcination time in S2 is 2 to 4 h;
[0016] Furthermore, the stirring time in S3 is 6 to 10 h;
[0017] Furthermore, the reaction temperature in the Teflon stainless steel high-pressure reactor in S3 is 200-300° C., and the reaction time is 10-24 h;
[0018] Furthermore, the temperature for drying overnight in S3 is 80°C.
[0019] The polyetheretherketone containing amino and carboxyl side groups is prepared by the following steps:
[0020] P1: Dry the polyetheretherketone powder in a vacuum drying oven;
[0021] P2: Pour the dried polyetheretherketone powder and sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100-160°C for 12-24 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in an acetic acid solution of 0.3 g / ml 4-aminobenzoic acid, stir at room temperature, and then wash it with acetic acid, deionized water and acetone in turn, and vacuum dry it after washing to obtain polyetheretherketone containing amino and carboxyl side groups;
[0022] Further, the drying temperature in P1 is 120-180°C;
[0023] Further, the drying time in P1 is 4 to 6 h;
[0024] Furthermore, the vacuum drying temperature in P2 is 80°C;
[0025] Furthermore, the vacuum drying time in P2 is 24 h;
[0026] Furthermore, the stirring time in P2 is 48 to 72 h.
[0027] A method for preparing the above-mentioned antistatic polyetheretherketone composite film comprises the following steps:
[0028] R1: Immerse In2O3•SnO2@CF in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, then perform ultrasonic immersion, retain the precipitate by centrifugation, wash the precipitate with deionized water and anhydrous ethanol, and dry overnight to obtain surface-treated In2O3•SnO2@CF;
[0029] R2: Surface-treated In2O3•SnO2@CF, polyetheretherketone containing amino and carboxyl side groups, silane coupling agent, lubricant, and film-forming agent are put into a high-speed mixer for mixing to obtain a premix, and then the obtained premix is put into a twin-screw extruder, and after extrusion, cooling, and pelletizing operations, composite pellets are obtained; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die, and prepared through a longitudinal traction stretching device to obtain an antistatic polyetheretherketone composite film;
[0030] Furthermore, the ultrasonic immersion time in R1 is 2 to 4 h;
[0031] Further, the temperature of drying overnight in R1 is 80°C;
[0032] Further, the mixing time in R2 is 30 min;
[0033] Furthermore, the extrusion temperatures of the twin-screw extruder and the single-screw extruder in R2 are both 350-380°C.
[0034] The antistatic polyetheretherketone composite film is applied to the preparation of antistatic films for integrated circuit chips and sensors inside mobile phones or small electronic devices.
[0035] Compared with the prior art, the present invention solves the problem of poor dispersibility of conductive fibers of a single form in polyetheretherketone materials in the prior art, and has the following specific beneficial effects:
[0036] 1. Significantly improve electrical conductivity: The present invention prepares a nano-carbon fiber loaded indium tin oxide composite material (In2O3•SnO2@CF) by coaxial spinning and solvothermal method. The composite material has an ultrafine hollow structure and a multi-layer porous structure. This structure significantly increases the specific surface area of the material, and more charge carriers can be gathered in a unit volume, thereby improving the overall electrical conductivity; at the microscopic level, its multi-layer porous structure also forms multiple conductive channels, allowing current to propagate freely inside it, effectively reducing the transmission resistance of electrons, enhancing the mobility of electrons, and promoting the rapid propagation of current, thereby significantly improving electrical conductivity.
[0037] 2. Enhanced interface bonding ability: The present invention prepares polyetheretherketone containing amino and carboxyl side groups through polymerization reaction, and utilizes the method that indium and tin metal ions in In2O3•SnO2@CF composite material can form stable coordination bonds with amino and carboxyl groups in polyetheretherketone containing amino and carboxyl side groups to prepare antistatic polyetheretherketone composite film, which significantly enhances the interface bonding ability between the two, effectively avoids the performance degradation caused by poor interface bonding, and further improves the stability and durability of the antistatic polyetheretherketone composite film; at the same time, its high conductivity characteristics significantly accelerate the static electricity consumption inside the material, effectively prevent the accumulation of static electricity, and ensure its antistatic performance during long-term use.
[0038] 3. Broad application prospects: The antistatic polyetheretherketone composite film prepared by the present invention has a wide range of application potentials and can be used in the preparation of integrated circuit chips and sensor covering films of mobile phones and small electronic devices. These applications can meet the increasingly stringent antistatic requirements and provide a strong guarantee for the safety and reliability of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1This is the schematic diagram of the preparation process of antistatic polyetheretherketone composite film;
[0040] Figure 2 Electrochemical properties of conventional carbon fiber and In2O3•SnO2@CF composites It Graphs;
[0041] Figure 3 This is the BET diagram of conventional carbon fiber and In2O3•SnO2@CF composite material. DETAILED DESCRIPTION
[0042] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0043] Example 1.
[0044] S1: Pour 20 g of polyacrylonitrile evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly for 8 h to obtain a precursor spinning solution; then pour 10 g of polyvinyl pyrrolidone evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly to obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, and pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, and control the flow rates of the two to be 0.1 mL / min and 0.2 mL / min respectively, the spinning voltage is 15 kV, and the distance from the double nozzle needle to the drum collector is 20 cm, then coaxial electrospinning is performed to collect the fiber filaments;
[0045] S2: The collected fiber filaments were placed in a crucible and transferred into a vacuum tube furnace. Under a nitrogen atmosphere, the temperature was raised to 550°C at a heating rate of 5°C / min, and then calcined at a constant temperature for 2 h. After the calcination, the fiber filaments were naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0046] S3: 20 g of hollow carbon fiber, 6.35 g of InCl3, and 3.66 g of SnCl4 were uniformly added into 500 ml of 50% ethanol aqueous solution and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2@CF;
[0047] S4: The In2O3•SnO2@CF prepared in S3 was immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80 °C overnight to obtain surface-treated In2O3•SnO2@CF;
[0048] S5: 80 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0049] S6: Pour 80 g of dried polyetheretherketone powder and 25 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0050] S7: 20 g of surface-treated In2O3•SnO2@CF, 80 g of polyetheretherketone containing amino and carboxyl side groups, 3 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent were put into a high-speed mixer and mixed for 30 min to obtain a premix; then the obtained premix was put into a twin-screw extruder and extruded at 375°C, and after cooling and pelletizing, composite pellets were obtained; finally, the obtained composite pellets were put into a single-screw extruder, extruded through a T-die at 375°C, and an antistatic polyetheretherketone composite film was prepared through a longitudinal traction stretching device, such as Figure 1 This is a schematic diagram of the preparation process of antistatic polyetheretherketone composite film.
[0051] Example 2.
[0052] S1: Pour 10 g of polyacrylonitrile evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly for 8 h to obtain a precursor spinning solution; then pour 5 g of polyvinyl pyrrolidone evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly to obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, and pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, and control the flow rates of the two to be 0.1 mL / min and 0.2 mL / min respectively, the spinning voltage is 15 kV, and the distance from the double nozzle needle to the drum collector is 20 cm, and then coaxial electrospinning is performed to collect the fiber filaments;
[0053] S2: The collected fiber filaments were placed in a crucible and transferred into a vacuum tube furnace. Under a nitrogen atmosphere, the temperature was raised to 550°C at a heating rate of 5°C / min, and then calcined at a constant temperature for 2 h. After the calcination, the fiber filaments were naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0054] S3: 10 g of hollow carbon fiber, 3.10 g of InCl3, and 1.83 g of SnCl4 were uniformly added into 500 ml of 50% ethanol aqueous solution and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2@CF;
[0055] S4: The In2O3•SnO2@CF prepared in S3 was immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80 °C overnight to obtain surface-treated In2O3•SnO2@CF;
[0056] S5: 90 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0057] S6: Pour 90 g of dried polyetheretherketone powder and 28 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0058] S7: Put 10 g of surface-treated In2O3•SnO2@CF, 90 g of polyetheretherketone containing amino and carboxyl side groups, 3 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent into a high-speed mixer and mix for 30 min to obtain a premix; then put the obtained premix into a twin-screw extruder, extrude it at 375°C, and obtain composite pellets after cooling and pelletizing; finally, put the obtained composite pellets into a single-screw extruder, extrude it through a T-die at 375°C, and prepare an antistatic polyetheretherketone composite film through a longitudinal traction and stretching device.
[0059] Example 3.
[0060] S1: Pour 30 g of polyacrylonitrile evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly for 8 h to obtain a precursor spinning solution; then pour 15 g of polyvinyl pyrrolidone evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly to obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, and pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, and control the flow rates of the two to be 0.1 mL / min and 0.2 mL / min respectively, the spinning voltage is 15 kV, and the distance from the double nozzle needle to the drum collector is 20 cm, then coaxial electrospinning is performed to collect the obtained fiber;
[0061] S2: The collected fiber filaments were placed in a crucible and transferred into a vacuum tube furnace. Under a nitrogen atmosphere, the temperature was raised to 550°C at a heating rate of 5°C / min, and then calcined at a constant temperature for 2 h. After the calcination, the fiber filaments were naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0062] S3: 10 g of hollow carbon fiber, 9.30 g of InCl3, and 5.50 g of SnCl4 were uniformly added into 500 ml of 50% ethanol aqueous solution and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2@CF;
[0063] S4: The In2O3•SnO2@CF prepared in S3 was immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80 °C overnight to obtain surface-treated In2O3•SnO2@CF;
[0064] S5: 70 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0065] S6: Pour 70 g of dried polyetheretherketone powder and 20 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0066] S7: 30 g of surface-treated In2O3•SnO2@CF, 70 g of polyetheretherketone containing amino and carboxyl side groups, 5 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent are put into a high-speed mixer and mixed for 30 min to obtain a premix; the obtained premix is then put into a twin-screw extruder and extruded at 375°C. After cooling and pelletizing, composite pellets are obtained; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die at 375°C, and an antistatic polyetheretherketone composite film is prepared through a longitudinal traction and stretching device.
[0067] Example 4.
[0068] S1: Pour 40 g of polyacrylonitrile evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly for 8 h to obtain a precursor spinning solution; then pour 20 g of polyvinyl pyrrolidone evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly to obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, and pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, and control the flow rates of the two to be 0.1 mL / min and 0.2 mL / min respectively, the spinning voltage is 15 kV, and the distance from the double nozzle needle to the drum collector is 20 cm, then coaxial electrospinning is performed to collect the obtained fiber;
[0069] S2: The collected fiber filaments were placed in a crucible and transferred into a vacuum tube furnace. Under a nitrogen atmosphere, the temperature was raised to 550°C at a heating rate of 5°C / min, and then calcined at a constant temperature for 2 h. After the calcination, the fiber filaments were naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0070] S3: 40 g of hollow carbon fiber, 12.40 g of InCl3, and 7.32 g of SnCl4 were uniformly added into 500 ml of 50% ethanol aqueous solution and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2@CF;
[0071] S4: The In2O3•SnO2@CF prepared in S3 was immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80 °C overnight to obtain surface-treated In2O3•SnO2@CF;
[0072] S5: 60 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0073] S6: Pour 60 g of dried polyetheretherketone powder and 18 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0074] S7: 40 g of surface-treated In2O3•SnO2@CF, 60 g of polyetheretherketone containing amino and carboxyl side groups, 5 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent are put into a high-speed mixer and mixed for 30 min to obtain a premix; the obtained premix is then put into a twin-screw extruder and extruded at 375°C. After cooling and pelletizing, composite pellets are obtained; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die at 375°C, and an antistatic polyetheretherketone composite film is prepared through a longitudinal traction and stretching device.
[0075] Comparative Example 1.
[0076] S1: Pour 20 g of polyacrylonitrile evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly for 8 h to obtain a precursor spinning solution; then pour 10 g of polyvinyl pyrrolidone evenly into 200 ml of N,N-dimethylformamide solution and stir thoroughly to obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, and pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, and control the flow rates of the two to be 0.1 mL / min and 0.2 mL / min respectively, the spinning voltage is 15 kV, and the distance from the double nozzle needle to the drum collector is 20 cm, then coaxial electrospinning is performed to collect the fiber filaments;
[0077] S2: The collected fiber filaments were placed in a crucible and transferred into a vacuum tube furnace. Under a nitrogen atmosphere, the temperature was raised to 550°C at a heating rate of 5°C / min, and then calcined at a constant temperature for 2 h. After the calcination, the fiber filaments were naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers.
[0078] S3: The hollow carbon fibers obtained in S2 were immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80 °C overnight to obtain surface-treated hollow carbon fibers;
[0079] S4: 80 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0080] S5: 20 g of surface-treated hollow carbon fibers, 80 g of polyetheretherketone powder, 3 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent were put into a high-speed mixer and mixed for 30 min to obtain a premix; the obtained premix was then put into a twin-screw extruder and extruded at 375°C, and composite pellets were obtained after cooling and pelletizing; finally, the obtained composite pellets were put into a single-screw extruder, extruded through a T-die at 375°C, and a polyetheretherketone composite film was prepared through a longitudinal traction stretching device.
[0081] Comparative Example 2.
[0082] S1: 10.33 g InCl3 and 6.08 g SnCl4 were uniformly added into 500 ml 50% ethanol aqueous solution and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2.
[0083] S2: 90 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0084] S3: Pour 90 g of dried polyetheretherketone powder and 28 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0085] S4: Put 10 g In2O3•SnO2, 90 g polyetheretherketone containing amino and carboxyl side groups, 3 g silane coupling agent, 3 g lubricant and 5 g film-forming agent into a high-speed mixer and mix for 30 min to obtain a premix; then put the obtained premix into a twin-screw extruder, extrude it at 375°C, and obtain composite pellets after cooling and pelletizing; finally, put the obtained composite pellets into a single-screw extruder, extrude it through a T-die at 375°C, and prepare the polyetheretherketone composite film through a longitudinal traction and stretching device.
[0086] Comparative Example 3.
[0087] S1: 20 g conventional carbon fiber, 6.40 g InCl3, and 3.66 g SnCl4 were uniformly added into 500 ml ethanol aqueous solution with a volume fraction of 50%, and stirred for 10 h. After stirring, the mixture was transferred into a Teflon stainless steel autoclave and reacted at 220 °C for 12 h. After the reaction, the precipitate was washed with anhydrous ethanol and deionized water, and then dried at 80 °C overnight to obtain In2O3•SnO2 modified conventional carbon fiber;
[0088] S2: The In2O3•SnO2 modified conventional carbon fiber prepared in S1 was immersed in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, ultrasonically immersed for 2 h, centrifuged to retain the precipitate, washed with deionized water and anhydrous ethanol, and then dried at 80°C overnight to obtain surface-treated In2O3•SnO2 modified conventional carbon fiber;
[0089] S3: 80 g of polyetheretherketone powder was placed in a vacuum drying oven and dried at 180 °C for 4 h;
[0090] S4: Pour 80 g of dried polyetheretherketone powder and 25 g of sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100°C for 18 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry at 80°C for 24 h to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 500 ml of 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature for 72 h, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it at 80°C for 8 h to obtain polyetheretherketone containing amino and carboxyl side groups;
[0091] S5: Put 20 g of surface-treated In2O3•SnO2-modified conventional carbon fiber, 80 g of polyetheretherketone containing amino and carboxyl side groups, 3 g of silane coupling agent, 3 g of lubricant and 5 g of film-forming agent into a high-speed mixer and mix for 30 min to obtain a premix; then put the obtained premix into a twin-screw extruder, extrude it at 375°C, and obtain composite pellets after cooling and pelletizing; finally, put the obtained composite pellets into a single-screw extruder, extrude it through a T-die at 375°C, and prepare the polyetheretherketone composite film through a longitudinal traction and stretching device.
[0092] Surface resistivity test:
[0093] The polyetheretherketone composite films provided in the above examples 1-4 and comparative examples 1-3 were cut into samples with a specification of 100×100×0.2 mm, and the surface resistivity of the samples was tested using a CZ-90F high resistance meter. The output voltage was set to 220 V, the current was 6 A, the frequency was 50 Hz, and the resistance range was 10 6 ~10 16 Ω, the results are shown in the following table. It can be seen from the table that the surface resistivity of the In2O3•SnO2@CF composite material prepared by the coaxial spinning method and the solvothermal method meets the antistatic requirements. The antistatic polyetheretherketone composite film prepared in Examples 1-4 is compared with the polyetheretherketone composite film prepared in Comparative Examples 1-3 with only hollow carbon fiber added (Comparative Example 1), only In2O3•SnO2 added (Comparative Example 2), and conventional carbon fiber loaded In2O3•SnO2 (Comparative Example 3). The unique structure and ultra-high conductivity of the In2O3•SnO2@CF composite material can accelerate the static electricity consumption inside the antistatic polyetheretherketone composite film, making the surface resistivity increase from 15.5 to 18.9×10 7 Ω is reduced to 7.81~9.7×10 7 Ω.
[0094]
[0095] Volt-ampere characteristic test:
[0096] 20 mg of conventional carbon fiber and In2O3•SnO2@CF composite were dispersed in a mixed solution of 2 mL ethanol and 2 μL naphthol, respectively, and ultrasonically dispersed for 20 min. Then 0.5 mL of the above suspension was evenly dropped on a 1×3 cm 2 On FTO glass substrate (active area 2 cm 2 ), the prepared electrode was dried naturally overnight at room temperature to obtain the working electrode. The test was carried out using a CHI760E electrochemical workstation, with Hg / Hg2Cl2 and Pt as the reference electrode and counter electrode respectively, and a 0.5 MNa2SO4 aqueous solution as the electrolyte. The response current value was recorded by intermittent power-on to obtain the following Figure 2 The linear volt-ampere characteristic curve shown ( It Curve). It can be seen from the figure that the response current of In2O3•SnO2@CF composite material is significantly higher than that of conventional carbon fiber, and the current response remains at a relatively stable level, proving that the ultrafine hollow structure and multi-layer porous structure of In2O3•SnO2@CF composite material increase the transmission channel of ions in the electrolyte, allowing the current to propagate freely inside it, effectively reducing the transmission resistance of electrons, enhancing the mobility of electrons, and improving the efficiency of electron transmission.
[0097] BET Test:
[0098] like Figure 3 The BET test results of conventional carbon fiber and In2O3•SnO2@CF composite material show that the BET specific surface area of In2O3•SnO2@CF composite material is 56.19 cm² / g, which is significantly higher than the BET specific surface area of conventional carbon fiber 23.63 cm² / g. This shows that by loading In2O3 and SnO2 nanoparticles on the surface of carbon fiber, the specific surface area of the composite material is effectively increased. The increase in specific surface area means that the In2O3•SnO2@CF composite material has more active sites, which is beneficial to improve the adsorption capacity and reaction activity of the material, thereby achieving a higher current response in electrochemical applications. In addition, the high specific surface area can also promote the diffusion and transport of ions in the electrolyte and increase the electrochemical reaction rate of the material.
[0099] In summary, the In2O3•SnO2@CF composite material prepared by the coaxial spinning method and the solvothermal method of the present invention has an increased specific surface area of the material due to its ultrafine hollow structure and multi-layer porous structure, and more charge carriers can be gathered in a unit volume, thereby improving the overall conductivity; at the same time, its multiple conductive channels allow the current to propagate freely inside it, effectively reducing the transmission resistance of electrons, enhancing the mobility of electrons, promoting the rapid propagation of current, and thus significantly improving the conductivity. The method of using the indium and tin metal ions in the In2O3•SnO2@CF composite material to form a stable coordination bond with the amino and carboxyl groups in the polyetheretherketone containing amino and carboxyl side groups, the prepared antistatic polyetheretherketone composite film significantly enhances the interface bonding ability between the two, effectively avoids the performance degradation caused by poor interface bonding, and further improves the stability and durability of the antistatic polyetheretherketone composite film; at the same time, its high conductivity characteristics significantly accelerate the static electricity consumption inside the material, effectively prevent the accumulation of static electricity, and ensure its antistatic performance during long-term use.
Claims
1. An antistatic polyetheretherketone composite film, characterized in that: The invention comprises the following components in parts by weight: 10-40 parts of In2O3•SnO2@CF, 60-90 parts of polyetheretherketone containing amino and carboxyl side groups, 1-3 parts of silane coupling agent, 1-3 parts of lubricant, and 3-10 parts of film-forming agent; The In2O3•SnO2@CF is prepared by the following steps: S1: Pour polyacrylonitrile evenly into N,N-dimethylformamide solution, stir thoroughly, and obtain a precursor spinning solution; then pour polyvinyl pyrrolidone evenly into N,N-dimethylformamide solution, stir thoroughly, and obtain a structural carrier emulsion; pass the structural carrier emulsion into a syringe connected to the inner channel of the double nozzle of the coaxial spinning machine, pass the precursor spinning solution into a syringe connected to the outer channel of the double nozzle of the coaxial spinning machine, perform coaxial electrospinning, and collect to obtain fiber filaments; S2: The collected fiber filaments are placed in a crucible and transferred into a vacuum tube furnace. The temperature is raised to 550°C in a nitrogen atmosphere and then calcined at a constant temperature. After the calcination, the fiber filaments are naturally cooled to room temperature, and then washed and dried with deionized water and anhydrous ethanol to obtain hollow carbon fibers. S3: The hollow carbon fiber, InCl3 and SnCl4 are uniformly added into a 50% ethanol aqueous solution and stirred. After the stirring, the mixture is transferred into a Teflon stainless steel high-pressure reactor for reaction. After the reaction, the precipitate is washed with anhydrous ethanol and deionized water and dried overnight to obtain In2O3•SnO2@CF; The polyetheretherketone containing amino and carboxyl side groups is prepared by the following steps: P1: PEEK powder is placed in a vacuum drying oven and dried; P2: Pour the dried polyetheretherketone powder and sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100-160°C for 12-24 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, and then vacuum dry to obtain polyetheretherketone with hydroxyl groups on the surface; immerse the polyetheretherketone with hydroxyl groups in 0.3 g / ml 4-aminobenzoic acid acetic acid solution, stir at room temperature, and then wash it with acetic acid, deionized water and acetone in turn, and then vacuum dry it after washing to obtain polyetheretherketone containing amino and carboxyl side groups.
2. The antistatic polyetheretherketone composite film according to claim 1, characterized in that: The stirring time in S1 is 2-8 h; the flow rates of the structural carrier emulsion and the precursor spinning solution are 0.1 mL / min and 0.2 mL / min, respectively; the spinning voltage of the coaxial electrospinning is 15-25 kV; and the distance from the double nozzle needle of the coaxial spinning machine to the drum collector is 10-25 cm.
3. The antistatic polyetheretherketone composite film according to claim 1, characterized in that: The heating rate in S2 is 5°C / min; the constant temperature calcination time is 2-4 h.
4. The antistatic polyetheretherketone composite film according to claim 1, characterized in that: The stirring time in S3 is 6-10 h; the reaction temperature in the Teflon stainless steel high-pressure reactor is 200-300° C., and the reaction time is 10-24 h; the temperature for drying overnight is 80° C.
5. The antistatic polyetheretherketone composite film according to claim 1, characterized in that: The drying temperature in P1 is 120-180° C., and the drying time is 4-6 h; the vacuum drying temperature in P2 is 80° C., the vacuum drying time is 24 h, and the stirring time is 48-72 h.
6. A method for preparing an antistatic polyetheretherketone composite film as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: R1: Immerse In2O3•SnO2@CF in an ethanol solution of a vinyl silane coupling agent with a volume fraction of 10%, then perform ultrasonic immersion, retain the precipitate by centrifugation, wash the precipitate with deionized water and anhydrous ethanol, and dry overnight to obtain surface-treated In2O3•SnO2@CF; R2: Surface-treated In2O3•SnO2@CF, polyetheretherketone containing amino and carboxyl side groups, silane coupling agent, lubricant and film-forming agent are put into a high-speed mixer to mix to obtain a premix, and then the obtained premix is put into a twin-screw extruder. After extrusion, cooling and pelletizing operations, composite pellets are obtained; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die, and an antistatic polyetheretherketone composite film is prepared through a longitudinal traction and stretching device.
7. The method for preparing the antistatic polyetheretherketone composite film according to claim 6, characterized in that: The ultrasonic immersion time in R1 is 2-4 h, and the overnight drying temperature is 80° C.; the mixing time in R2 is 30 min, and the extrusion temperatures of the twin-screw extruder and the single-screw extruder are both 350-380° C.
8. An application of an antistatic polyetheretherketone composite film prepared by the preparation method according to any one of claims 1 to 5 or any one of claims 6 to 7, characterized in that: It is used in the preparation of antistatic films for integrated circuit chips and sensors inside mobile phones or small electronic devices.
Citation Information
Patent Citations
Polyetheretherketone-base composite, preparing method thereof and application thereof in friction reduction and wear resistance
CN104927298A
Preparation of ZIF-8 / polyetheretherketone and ZIF-8 @GO / polyetheretherketone anion composite membrane
CN113178602A